Resocialization of Inmates in Half-Way Houses of Prisons: Experience of Inmates - Gerybaitė, Gintarė (Socialinė teorija, empirija, politika ir praktika, 2025)
Since 2016, part of the process of resocialization of inmates has been implemented by the half-way house institute. The article reveals the results of an exploratory study on the resocialization of convicts who continue their prison sentences in half-way houses. The issues raised in this article are related to the implementation of resocialization measures in the half-way houses, factors influencing the resocialization in the half-way houses, and the prospects for the development of quality-based resocialization in the half-way houses. The research has revealed the possible significance of the resocialization in the half-way houses for the inmate, the importance of staff assistance, and the peculiarities of resocialization activities in the half-way house. An inmate getting transferred to a half-way house is associated with proof of the progress made along with an opportunity to start a new life. The factors revealed by the study which possibly facilitate the preparation for the return to society from the half-way house are associated with half-way house staff and open prison conditions. The research has identified the possible perspectives and developments of the practices applied in the half-way house. The list of possible developments includes the improvement of the physical conditions in the half-way house. Also, the improvement of the rules of the internal order and the introduction of new measures for the inmates in the half-way house have been distinguished as promising directions for further developments.